Peran Lembaga Perlindungan Anak dalam Sistem Hukum Pidana terhadap Anak yang Berhadapan dengan Hukum - Kartika, Dessy; Dumillah, Dewic Sri Ratnaning (HUMANIORUM, 2025)
This study examines the role of the Child Protection Agency (LPA) in the criminal justice system concerning children who come into conflict with the law. The research aims to analyze the legal framework and practices surrounding the protection and rehabilitation of children in conflict with the law. By using a normative legal approach, the study explores the implementation of restorative justice principles and the challenges faced by LPA in advocating for children’s rights during the judicial process. The findings highlight the critical function of LPA in supporting diversion, mediation, and rehabilitation programs, despite encountering barriers such as limited resources and lack of coordination with law enforcement agencies. This study employs a qualitative method with literature review and descriptive analysis to evaluate primary and secondary legal sources. The results indicate that while LPA plays a significant role, several gaps in the legal framework and practical implementation need to be addressed to enhance the protection of children in the criminal justice system. The study suggests improvements in coordination between LPA and law enforcement agencies, increased funding for LPA, and public education to reduce stigma against children in conflict with the law. In conclusion, strengthening the capacity of LPA is essential to ensuring the fair treatment of children and the effective application of restorative justice principles in the criminal justice process.